EFFECT OF LEAVES EXTRACT OF IPOMOEA CAIRICA ON CHLOROPHYLL AND CAROTENOID IN PARTHENIUM HYSTEROPHOROUS L. - Srivastava, Deepa; Shukla, K. (International Journal of Research -GRANTHAALAYAH, 2016)
Photosynthetic effects of the leaves extracts from Ipomoea cairica on Partheniumhysterophorus L were studied. Ipomoea cairica dried leaf powder (20g) was dissolved in distilled water (200ml) for foliar application. The seedlings were maintained under natural condition in Insect free net house. The experiment was carried out to analyze the effects of Ipomoea cairica leaves extract by measuring chlorophyll ‘a’, chlorophyll ‘b’, total chlorophyll and carotenoid contents in Parthenium. The experimental plants were sprayed 20 days after emergence and control plants were maintained by a simultaneous spray of distilled water. Leaves of Partheniumhysterophorus were collected at 5 days interval following the foliar application of Ipomoea cairica leaves extract up to 15th day. Results showed that Chlorophyll (total chlorophyll, chlorophyll a and b) and carotenoid content was adversely affected as the duration of Ipomoea cairica leaves extract increased. This potential of Ipomoea cairica can be used as herbicide to control noxious weed Partheniumhysterophorous.